The Impact of China's Belt and Road Initiative on Indonesia's Export to China - Diah Ayu Wulandari; Asmia Inayah (Journal of World Trade Studies, 2021)
This study examines the difference between Indonesia's export to China before and after Indonesia's engagements with the Belt and Road Initiative (BRI). It compares Indonesia's export to China between 2007-2013 and 2014-2020 to assess the change. This research uses a comparative and descriptive quantitative approach. The authors use the Kolmogrov-Smirnov Normality test and the Paired T test. Based on the Paired T Test calculation, it demonstrates that there is a difference between Indonesia's export to China before and after the BRI project, in that Indonesia's export to China increased after its engagements with BRI. In conclusion, the BRI positively impacts Indonesia's export to China.